Coastal erosion study of Ponnani region using multispectral images - SHEEJA P. S (Tavanur 2015 DEPARTMENT OF IRRIGATION AND DRAINAGE ENGINEERING)
the objectives of this study to determine the temporal shoreline changes along the coastal areas of Ponnani using remote sensing and digital change detection techniques and to study the extent and magnitude of the coastal erosion occured to identify priority areas and suggest suitable preventive measures were met. The coastal erosion study using remote sensing and GIS techniques provided realistic information about the erosion process along Ponnani area and this method can be successfully used for mapping and monitoring coastal changes.
Coastal erosion study of Ponnani region using multispectral images